Studi Pengenalan Internet of Things Bagi Guru dan Siswa SMK Bina Nusa Slawi Sebagai Wawasan Salah Satu Ciri Revolusi Industri 4.0 - Ginanjar Wiro Sasmito; Sena Wijayanto; La Ode Mohamad Zulfiqar (Universitas Lancang Kuning, 2020)
Bina Nusa Slawi Vocational School (Binus) is one of the Vocational High Schools located in Slawi District, Tegal Regency. The results of a survey conducted, that almost all teachers and students (99%) had heard about the Industrial Revolution 4.0 and Internet of Things, but did not understand the meaning of it all, even though the industrial revolution 4.0 had disrupted almost all fields of science and lines of life. The survey results also show that all teachers and students have used internet maximally, but development trend of the use internet that is not yet widely understood, especially regarding: Wireless Sensor Network (WSN), Cloud Computing, Big Data, and Artificial Intelligence. Therefore needed an Introduction Study Internet of Things for Teachers and Students of SMK Bina Nusa Slawi as Insights One of the Characteristics of the Industrial Revolution 4.0. The method implemented is by giving presentations, discussions, and demonstrations about Internet of Things, Artificial Intelligence and Big Data. Based on activities that have been carried out, the results obtained are knowledge, understanding, competence of teachers and students of SMK Bina Nusa Slawi about Internet of Things increasing.